Law, psychology, and morality : the role of loss aversion - Zamir, Eyal (New York : Oxford University Press, 2014)
Prospect theory posits that people do not perceive outcomes as final states of wealth or welfare, but rather as gains or losses in relation to some reference point. People are generally loss averse: the disutility generated by a loss is greater than the utility produced by a commensurate gain. Loss aversion is related to such phenomena as the status quo and omission biases, the endowment effect, and escalation of commitment. The book systematically analyzes the relationships between loss aversion and the law.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on October 28, 2014).
Keywords: Law and economics; Economics -- Psychological aspects; Actions and defenses -- Psychological aspects; Loss aversion; Cognitive psychology